Case report: Type 2 diabetes mellitus with plantar malignant melanoma: Report of two cases - Huang, Bi-Ling; Tan, Min; Li, Ming-Liu; Teng, Yuan-Yuan; Zhou, Min; Wang, Min (Frontiers in Oncology, 2023)
Malignant melanoma is a highly malignant tumor that originates from melanocytes. It has a poor prognosis and rarely occurs on the foot. Diabetic foot ulcer is one of the most serious chronic complications of diabetes. This paper reports two cases of type 2 diabetes patients with malignant melanoma on the foot. Clinicians should improve their understanding of patients with diabetes with acral malignant melanoma. When diabetic foot ulcers occur repeatedly and continue not to heal, the clinical features of the cutaneous lesions are similar to malignant melanoma, and a pathological biopsy of the lesions should be performed promptly to obtain a clear diagnosis, avoid a missed diagnosis and improve the survival rate.